Pembinaan Jurnalistik untuk Meningkatkan Minat Menulis pada Santri di Dayah Darul Muta’alimin Meulaboh - Reni Juliani; Putri Maulina (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Santri (student) also plays an important role in writing to convey information about Islamic teachings. For this reason, students need knowledge of journalism in order to develop their intellectual potential. Therefore, journalistic guidance needs to be carried out to increase student interest in writing. This is useful for teaching students how good journalism is and based on journalistic principles. The result of this nonprofit activity was that Students of Dayah Darul Muta'alimin learned about real journalism, they knew how good the news was, and they realized that facts and data must be guaranteed to be true.